HUBUNGAN KADAR ASAM URAT DENGAN TEKANAN DARAH PADA REMAJA OBESITAS DI KOTA SEMARANG - Monikasari, Monikasari; Ardiaria, Martha; Widyastuti, Nurmasari (Journal of Nutrition College, 2017)
Background : Obesity in adolescents may cause elevated uric acid levels, leading to increased blood pressure. This occurs as a result of high uric acid levels inducing arteriolopathy in preglomerular vessels. Consequently, the autoregulator response of the afferent arterioles is impaired and eventually causing hypertension. This study aimed to determine the association of uric acid levels with blood pressure in obese adolescents. Adolescent with hypertension could continue in adulthood and had an higher increased risk of mortality. Objective : To analyze correlation of serum uric acid with blood pressure in obese adolescent in SemarangMethods : This was an observational, cross-sectional study with fifty-three subjects selected through consecutive sampling. Food intakes were assessed using Semi Quantitative Food Frequency Questionare. Serum uric acid levels were measured by Uricase PAP, while physical activity levels were determined by Short International Physical Activity Questionare. Data were analyzed using Rank-Spearman test. Result : Mean serum uric acid levels in male adolescents was 4.897±1.223 mg/dL with an average systolic blood pressure of 1.219±9.544 and a mean diastolic blood pressure of 85.85±8.359. In female subjects, the mean serum uric acid levels was 4.841±0.883 mg/dL with an average systolic blood pressure of 1.175±9.653 and an average diastolic blood pressure of 81.67±8.348. Serum uric acid levels were significantly correlated with systolic blood pressure (p = 0.000; r=0,495) and diastolic blood pressure (p = 0.010, r=0,325).Conclusion : Serum uric acid levels were significantly correlated with blood pressure among obese adolescents in Semarang.